2016
DOI: 10.1002/mus.25164
|View full text |Cite
|
Sign up to set email alerts
|

Rasch analysis of the Pediatric Evaluation of Disability Inventory–computer adaptive test (PEDI‐CAT) item bank for children and young adults with spinal muscular atrophy

Abstract: The PEDI-CAT may be used to measure functional performance in SMA, but additional items are needed to identify small changes in function and best represent the abilities of all types of SMA. Muscle Nerve 54: 1097-1107, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Further, while two of the five domain comparisons revealed that significantly more participants scored at the floor on the PEDI-CAT, the remaining three domain comparisons were not significantly different between the PEDI-CAT and VABS-3. Other studies have also found that there are elevated floor effects using the PEDI-CAT in populations with significant functional needs [ 31 , 39 ] and likely represents insufficient items at the lower end of the assessments. These results highlight the need for additional measures or the validation of new scoring methods for both of these measures if adaptive domains are included in a research trial, as these measures would not likely capture changes well for this lower functioning subset of patients with the current scoring systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, while two of the five domain comparisons revealed that significantly more participants scored at the floor on the PEDI-CAT, the remaining three domain comparisons were not significantly different between the PEDI-CAT and VABS-3. Other studies have also found that there are elevated floor effects using the PEDI-CAT in populations with significant functional needs [ 31 , 39 ] and likely represents insufficient items at the lower end of the assessments. These results highlight the need for additional measures or the validation of new scoring methods for both of these measures if adaptive domains are included in a research trial, as these measures would not likely capture changes well for this lower functioning subset of patients with the current scoring systems.…”
Section: Discussionmentioning
confidence: 99%
“…The PEDI-CAT has been translated and cross-culturally adapted into several versions, including Spanish, Dutch and Brazilian-Portuguese [ 19 , 20 ]. It has been used to assess motor functioning in children with learning disorders and children with spina bifida, as well as all domains of functioning in autism spectrum disorder (ASD), Down syndrome, cerebral palsy, Angelman syndrome, infants and toddlers receiving EI services and many others [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Several studies show strong psychometric evidence for the PEDI-CAT.…”
Section: Introductionmentioning
confidence: 99%
“…The PEDI‐CAT in school aged children has been found to have strong construct validity and reliability (Shore et al, ). However Pasternak et al () found that it lacks sensitivity for measuring skills and progress in children with significant functional needs even when using all the item bank questions rather than the computer generated ones.…”
Section: Discussionmentioning
confidence: 99%
“…Principal component analysis (PCA) on the residuals of the Rasch model verified the unidimensionality of the DA and MB domains. According to the criterion adopted by Pasternak et al [21], the amount of variance explained by the first dimension should be > 20% to consider the data to be one-dimensional.…”
Section: Data Analysesmentioning
confidence: 99%
“…Strong psychometric properties of the PEDI-CAT have been documented for individuals with and without disabilities [15][16][17]. Its application so far includes the evaluation of functioning in children and young people with autism spectrum disorders [18], complex medical conditions [19], HIV encephalopathy [20] and spinal muscular atrophy [21].…”
mentioning
confidence: 99%